Takhrij and Syarah Hadith of Chemistry The Coumpound Content in Olive and Their Suitability in The Hadith - Amirah Firyal Humaira; Wahyudin Darmalaksana; Tatang Zakaria; Vina Amalia (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this research is to discuss the hadith of the Prophet Muhammad regarding olive plants. This research method is qualitative through the approaches of takhrij and sharah hadith with chemical analysis. The results and discussion of this study is an olive plant already known from the time of Muhammad SAW. There are several hadiths that mention about olive. Olives are known for its benefits. Olives contain many compounds that are good for the body when consumed. The conclusion of this study is takhrij and syarah hadith of the Prophet about olive plants with chemical analysis containing compounds that are good for the body.